NATIONAL SECURITY POLICY OF ITALY (Annual of the Faculty of Philosophy in Skopje, 2020)
The security policy of the Republic of Italy serves as a key framework for the realizationof fundamental interests in the country. There is no doubt that Italy's securitypolicy has a specific place, given that it unites the country's overall efforts to adequatelyrespond to threats. Undoubtedly, this contributes to the formation of security measures,to the action of the security sector within the constitutionally permitted framework. Atthe same time, security policy enables political goals to grow into a political security doctrinethat seeks to produce an optimal concept and strategy of action to achieve the setgoals. The complexity, variability and interdependence of the security system and securitypolicy is the reason why these two segments in Italy have been analysed in one place.The analysis is supported by many questions and analogous to many answers related tothe creation of security policy and the conditions in which it is realized.
Keywords: SECURITY; NATIONAL SECURITY; POLICY; SECURITY POLICY; ITALY